Foreign EU elderly citizens before the polls: the 2015 local elections in Spain - Durán, Rafael (My University, 2017)
Ageing, European integration and human mobility beyond national frontiers are three intertwined processes shaping Spain as an international retirement place. Insofar as the quality of democracy has to do with citizens’ political involvement, the aim of this paper is to analyse to what extent foreign EU retirees residing in Spain are using their right to vote in the local elections. Interestingly, the last local elections, held in 2015, were part of a substantial change of the Spanish party system throughout the Great Recession. However, gerontomigrants’ mobilization has not been addressed up to this moment. This empirical study focuses on the characteristics and intensity in which foreign elderly citizens mobilized in the last Spanish local elections, with special attention to EU seniors. The previous elections, held in 2011, will be examined from a comparative perspective. Main data to be analysed will mostly be provided by the Spanish National Statistics Institute (INE) – both the electoral register and the population census. They will be complemented with the MIRES3i survey, which, in 2011, addressed 720 foreign European retirees (pensioners aged 50 years and over) of 16 nationalities (those of the EU-15 plus those coming from Norway and Switzerland) living in Spain.
Keywords: Emigración e inmigración - Paises de la Unión Europea; Migration; Elections; Spain; European Union; Ageign; Gerontomigration; International Retirement Migration; Political participation; Representation; Democracy